Variation From an Unknown Source: Large Inter-individual Differences in Migrating Black-Tailed Godwits - Verhoeven, Mo A.; Loonstra, A. H. Jelle; Senner, Nathan R.; McBride, Alice D.; Both, Christiaan; Piersma, Theunis (Frontiers in Ecology and Evolution, 2019)
Variation in migratory behaviour is the result of different individual strategies and fluctuations in individual performances. A first step toward understanding the variation among individuals is therefore to assess the relative contributions of inter- and intra-individual differences to this variation. We did this using light-level geolocators deployed on the breeding grounds to follow continental black-tailed godwits (Limosa limosa limosa) throughout both their south- and northward migrations over multiple years. Based on repeated tracks from 36 individuals, we found two general patterns in godwit migratory behaviour: First, migratory timing in black-tailed godwits varies mostly because individual godwits migrate at different times of the year. Second, individuals also exhibit considerable variation in timing within their respective migratory windows. Although the absolute amount of inter-individual variation in timing decreased over the course of northward migration, individual godwits still arrived at their breeding grounds across a span of more than five weeks. These differences in migratory timing among individuals are larger than those currently observed in other migratory bird species and suggest that the selective forces that limit the variation in migratory timing in other species are relaxed or absent in godwits. Furthermore, we could not attribute these individual differences to the sex or wintering location of an individual. We suggest that different developmental trajectories enabled by developmental plasticity likely result in these generally consistent, life-long annual routines. To investigate this possibility and to gain an understanding of the different selection pressures that could be at play during migration and throughout a godwit’s life, future studies should track juvenile godwits and other migratory birds from birth to adulthood while also manipulating their spatiotemporal environment during development.